In Situ Biodiesel Production from Fast-Growing and High Oil Content Chlorella pyrenoidosa in Rice Straw Hydrolysate. (17th January 2011) - Li, Penglin; Miao, Xiaoling; Li, Rongxiu; Zhong, Jianjiang
Abstract : Rice straw hydrolysate was used as lignocellulose-based carbon source for Chlorella pyrenoidosa cultivation and the feasibility of in situ biodiesel production was investigated. 13.7 g/L sugar was obtained by enzymatic hydrolyzation of rice straw. Chlorella pyrenoidosa showed a rapid growth in the rice straw hydrolysate medium, the maximum biomass concentration of 2.83 g/L was obtained in only 48 hours. The lipid content of the cells reached as high as 56.3%. In situ transesterification was performed for biodiesel production. The optimized condition was 1 g algal powder, 6 mL n -hexane, and 4 mL methanol with 0.5 M sulfuric acid at the temperature of 90 ° C in 2-hour reaction time, under which over 99% methyl ester content and about 95% biodiesel yield were obtained. The results suggested that the method has great potential in the production of biofuels with lignocellulose as an alternative carbon source for microalgae cultivation.